Development of E-Module for Balakka Plants (Phyllanthus emblica L.) Based on Local Potential - Melida Rangkuti; Efrida Pima Sari Tambunan; Khairuddin (Marga: Journal Of Innovation and Creatifity, 2024)
This research aims to produce learning media in the form of teaching materials for Class The type of research used is the ADDIE Research and Development model with development stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The assessment instrument consists of five instruments, namely the validity of the media expert instrument, the validity of the material expert instrument, the practicality test instrument by the teacher, the practicality test instrument by students, and the learning test. Based on the validation results by two validators, the final media validation value was 98.14% with the very valid category, and the final material validation value was 80.30% with the valid category. The practicality score based on the teacher's response was obtained at 87.50% with a very valid category and the student response obtained a score of 81.30% stating that the learning media in the form of teaching materials is very practical to use in learning. Finally, the effectiveness test was obtained based on the student learning outcomes test, it was found that it had an effectiveness of 60.22% with a fairly effective category which was reviewed using the N-Gain effectiveness interpretation category grouping, which means that the e-Module was effectively used in the learning process.